Uncovering the ‘saintly Anchoress’: myths of Medieval anchoritism and the reclusion of Katharine de Audley - Liz Herbert McAvoy (Women's History Review, 2013)
This article uncovers the lost history of the early fourteenth-century religious recluse, Katharine de Audley, a woman whose life came to be both distorted and romanticised by legend and literary adaptation in the centuries that followed. Tracing first the various literary treatments of Katharine as medieval anchorite, and second, her lived history as it emerges from the records, and by placing both within the historical and ideological context of medieval anchoritism, I argue for the female anchorite as forming part of a critical practice which continued to address socio-religious and personal needs both in her own day and long after she and her vocation had fallen from immediate cultural consciousness.